Mechanisms Linking Excess Adiposity and Carcinogenesis Promotion - Pérez-Hernández, Ana I.; Catalán, Victoria; Gómez-Ambrosi, Javier; Rodríguez, Amaia; Frühbeck, Gema (Frontiers in Endocrinology, 2014)
Obesity constitutes one of the most important metabolic diseases being associated to insulin resistance development and increased cardiovascular risk. Association between obesity and cancer has also been well-established for several tumor types, such as breast cancer in postmenopausal women, colorectal and prostate cancer. Cancer is the first death cause in developed countries and the second one in developing countries, with high incidence rates around the world. Furthermore, it has been estimated that 15-20% of all cancer deaths may be attributable to obesity. Tumor growth is regulated by interactions between tumor cells and their tissue microenvironment. In this sense, obesity may lead to cancer development through dysfunctional adipose tissue and altered signaling pathways. In this review, three main pathways relating obesity and cancer development are examined: i) inflammatory changes leading to macrophage polarization and altered adipokine profile; ii) insulin resistance development; and iii) adipose tissue hypoxia. Since obesity and cancer present a high prevalence, the association between these conditions is of great public health significance and studies showing mechanisms by which obesity lead to cancer development and progression are needed to improve prevention and management of these diseases.